The Giffen good — a praxeological approach - Wysocki, Igor; Block, Walter E. (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
In the present paper, we argue that the shape of any respectable demand curve must be monotonic (non-increasing). By doing so, we follow the footsteps of Murray Rothbard, who regarded the demand curve as derived from the law of diminishing marginal utility. However, our caveat is that the horizontal axis must represent the units of the same economic good. Equipped with the notion of the same economic good, we also argue that Giffen or Veblen goods do not pose any real problem for analysis. Rather, they behave as any other good — that is the demand curve for them is also (and necessarily) downward sloping
Keywords: popyt; prakseologia; krzywa popytu